2017
DOI: 10.1063/1.4976200
|View full text |Cite
|
Sign up to set email alerts
|

Wavepackets in inhomogeneous periodic media: Effective particle-field dynamics and Berry curvature

Abstract: Abstract. We consider a model of an electron in a crystal moving under the influence of an external electric field: Schrödinger's equation with a potential which is the sum of a periodic function and a general smooth function. We identify two dimensionless parameters: (re-scaled) Planck's constant and the ratio of the lattice spacing to the scale of variation of the external potential. We consider the special case where both parameters are equal and denote this parameter ǫ. In the limit ǫ ↓ 0, we prove the exi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…The bound (3.6) follows immediately from (3.2). When we consider the dynamics of wavepackets associated with E n (p) or E n+1 (p) and spectrally localized close to p * , the gap condition (3.2) and Corollary 3.3 will allow us to bound contributions to the solution from all bands other than E n (p) and E n+1 (p) uniformly through the crossing time, see Appendix D of [47] for details.…”
Section: Statement Of Results On Dynamics At Band Crossingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bound (3.6) follows immediately from (3.2). When we consider the dynamics of wavepackets associated with E n (p) or E n+1 (p) and spectrally localized close to p * , the gap condition (3.2) and Corollary 3.3 will allow us to bound contributions to the solution from all bands other than E n (p) and E n+1 (p) uniformly through the crossing time, see Appendix D of [47] for details.…”
Section: Statement Of Results On Dynamics At Band Crossingsmentioning
confidence: 99%
“…asymptotics is known to be the general limiting time-scale of validity of wavepacket, or coherent state, approximations [41]. These results generalize to d-dimensional analogs of (1.1) [47,6], see also [24,25,39].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For multiband wave packets, especially when there are crossing points in the band structure, this issue is currently under investigation. Recent studies have shown that the collapse time of a packet initially localized in a single band whose evolution allows interband transitions after encountering a crossing point is also relatively long and it is determined by the 1/h scale [23,24]. Also, it has been shown that a multiband description of a wave packet on a generic honeycomb potential with Dirac points accurately approximates the full solution to the Schroedinger equation for large times even when the packet is centered at the crossing point [25].…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Also, in a transport calculation, which includes scattering (not considered here), the time scale for spreading of the packet in real space must be larger than the scattering time. The collapse of the packet in reciprocal space is currently under investigation as noted earlier, although it has been shown that even for multiband wave packets with crossing points in the band structure, the collapse times are relatively long [22][23][24][25]32]. Although this issue needs further separate investigations, the EOM for the pair of linear bands can be obtained as…”
mentioning
confidence: 99%